Influence of the bottom metal electrode and gamma irradiation effects on the performance of HfO2-based RRAM devices. Issue 1 (1st February 2019) - Arun, N.; Vinod Kumar, K.; Mangababu, A.; Nageswara Rao, S. V. S.; Pathak, A. P.
ABSTRACT: Hafnium oxide-based Resistive Random Access Memory (RRAM) devices have been fabricated with Ag as the top electrode. Au and Pt have been used as bottom electrodes in two different sets to study the effects of oxidation on the performance of RRAM devices. Further, the influence of gamma irradiation on the performance of these devices has also been studied. It is shown that the diffusion of O vacancies and oxidation at electrodes are more effective for the migration of metal ions from the top electrode in determining the switching behavior of these devices. Pt-based devices are found to be more susceptible to gamma irradiation when compared to Au-based devices. The performance of the device is improved for lower doses (12 kGy), may be due to possible irradiation-induced annealing effects. Significant deterioration is observed at 24 kGy and the devices have totally failed at a dose of 48 kGy. These studies provide useful information about the radiation damage and reliability of HfO2 -based RRAM devices.